Homology and functions of inner staminodes in Anaxagorea javanica (Annonaceae). Issue 6 (10th November 2020) - Li, Bingxin; Xu, Fengxia
Abstract: Inner staminodes are widespread in Magnoliales and present in Anaxagorea and Xylopia, but were lost in the other genera of Annonaceae and have no counterparts in derived angiosperms. The coexistence of normal stamens, modified stamens and inner staminodes in Anaxagorea javanica is essential to understand the homology and pollination function of the inner staminodes. Anaxagorea javanica was subjected to an anatomical study by light and scanning electron microscopy, and the chemistry of secretions was evaluated by an amino acid analyser. Inner staminodes have a secretory apex, but do not have thecae. They bend towards either tepals or carpels at different floral stages, and function as a physical barrier preventing autogamy and promoting outcrossing. At the pistillate phase, the exudates from the inner staminodes have high concentration of amino acid, and provide attraction to pollinating insects; while abundant proline was only detected in stigmas exudates, and supply for pollen germination. Modified stamens have a secretory apex and one or two thecae, which are as long as or shorter than that of the normal stamens. As transitional structures, modified stamens imply a possible degeneration progress from normal stamens to inner staminodes: generating a secretory apex first, shortening of the thecae length next and then followed by the loss of thecae. The presence of modified stamens together with the floral vasculature and ontogeny imply that the inner staminodes are homologous with stamens. Abstract : Inner staminodes are widespread in Magnoliales and present in Anaxagorea and Xylopia, but were lost in the other genera of Annonaceae and have no counterparts in derived angiosperms. This paper demonstrates that the inner staminodes are homologous with stamens in Anaxagorea by documenting the existence of modified stamens with reduced thecae and secretory structures, and similar vasculature and phyllotactic continuity of stamens and staminodes as well. This paper also provides original data on floral phenology and chemical exudates of the staminodes and stigmas, which confirm the function of the staminodes during pollination in preventing autogamy.